Peran Mediasi Kesadaran akan Penampilan terhadap Niat Pembelian Produk Perawatan Kulit pada Pria Generasi Z - Fhakhir Nur Al Fidha; Siti Aisyah; Aqwa Naser Daulay (Value : Jurnal Manajemen dan Akuntansi, 2026)
This study examines the influence of masculinity perception and social media exposure on men’s skincare purchase intention, with appearance awareness as a mediating variable. The research addresses the issue that men’s skincare purchase intention is not only shaped by product promotion, but also by identity construction and self-evaluation of appearance. A quantitative survey approach was employed involving 262 male Generation Z university students in Medan City. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that masculinity perception has a positive effect on appearance awareness, but does not directly affect purchase intention. Social media exposure has a positive effect on both appearance awareness and purchase intention. Appearance awareness also has a positive effect on purchase intention. Furthermore, appearance awareness fully mediates the relationship between masculinity perception and purchase intention, and partially mediates the relationship between social media exposure and purchase intention. These findings indicate that men’s skincare purchase intention is formed through the interaction of masculine identity, digital exposure, and awareness of appearance. Practically, skincare companies need to develop marketing messages that connect skincare use with modern masculinity, healthy skin, confidence, and well-groomed appearance.